COMPARATIVE STUDY OF CURRICULUM 2013 AND THE MERDEKA CURRICULUM IMPLEMENTATION IN INDONESIAN ELEMENTARY SCHOOLS: INSIGHTS FROM DESCRIPTIVE-ANALYTICAL RESEARCH - Parade, Sindi Aulia Balqis; Amelia, Silvia; Fitriani; Oktavia, Sevti; Afriantoni (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
This study compares the implementation of the 2013 Curriculum (K13) and the Merdeka Curriculum in Indonesian elementary schools, focusing on structure, pedagogy, assessment, and teacher roles. Using a descriptive-qualitative approach, data were collected through interviews, classroom observations, and document analysis involving two teachers. Findings reveal that K13 is rigid and content-based with a mechanistic 5M scientific method, whereas the Merdeka Curriculum is flexible, competency-based, and emphasizes project learning and formative assessment. Teacher roles in Merdeka shift toward active facilitation. The Merdeka Curriculum proves more effective in fostering student independence and critical thinking. The novelty lies in its contextual classroom-based analysis, offering strategic insights for policy and teacher development. Penelitian ini membandingkan implementasi Kurikulum 2013 (K13) dan Kurikulum Merdeka di sekolah dasar Indonesia, dengan fokus pada struktur, pendekatan pembelajaran, sistem penilaian, dan peran guru. Menggunakan metode deskriptif-kualitatif, data dikumpulkan melalui wawancara, observasi kelas, dan analisis dokumen terhadap dua guru dari sekolah yang menerapkan masing-masing kurikulum. Hasil menunjukkan bahwa K13 bersifat kaku dan berorientasi konten dengan pendekatan saintifik 5M yang mekanis, sementara Kurikulum Merdeka lebih fleksibel, berbasis kompetensi, dan mendorong pembelajaran proyek serta penilaian formatif. Peran guru dalam Kurikulum Merdeka lebih sebagai fasilitator aktif. Temuan menunjukkan Kurikulum Merdeka lebih efektif dalam membangun kemandirian dan berpikir kritis siswa. Kebaruan studi ini terletak pada analisis kontekstual praktik kurikulum di kelas nyata, memberikan masukan strategis bagi pengembangan kebijakan dan pelatihan guru.